Impacts of geomechanical damage on waterflood-induced fracture propagation in deeply deposited tight oil reservoirs - Ding, Zhenfeng; Ge, Chenqi; Chen, Zhewei; Ji, Dongqi; Peng, Yingfeng; Zhang, Guangming; Hou, Yanan; Zhang, Jingzhou (Frontiers in Energy Research, 2024)
Waterflood-induced fractures can enhance the production of deep tight oil reservoirs.However, if waterflood-induced fractures propagate fast, they connect injection wells to production wells earlier, inhibiting the production of tight oil reservoirs. In the present research, the fast propagation mechanism of waterflood-induced fractures was mainly investigated. The changes in sandstone mechanical properties by water were investigated by laboratory experiments, and the relationship of the geomechanical damage of sandstones with water saturation was quantified. Flow-geomechanics-coupled numerical simulations were performed to analyze the impacts of water flooding on stress distribution in a deeply deposited tight oil reservoir. Based on the fracture mechanics theory, the propagation length of the waterflood-induced fracture was calculated and the characteristics of waterflood-induced fracture propagation were analyzed.Experimental results revealed that water changed the mineral composition and microscopic structure of sandstones. This phenomenon decreased the Young's modulus and tensile strength of sandstones and increased the Poisson's ratio. The changing magnitude of these properties increased with the rise of water saturation, and the maximum changing magnitude reached 70%.The water saturation distribution became heterogeneous after waterflooding, causing a heterogeneous distribution of mechanical properties. The stress around the fracture tip and the fracture propagation length were significantly affected by these property changes. After the geomechanical damage, the fracture propagation pressure decreased by about 20%. Moreover, the initial fracture length enhanced the propagation length of the waterflood-induced fracture. These results suggest that the propagation of waterflood-induced fractures becomes more significant during waterflooding; thus, the injection pressure should be reduced to avoid fast fracture propagation.